Розробка маркетингової стратегії промислового підприємства щодо забезпечення конкурентоспроможності на ринку - Федоренко, Ірина Анатоліївна; Анпілогова, А. В. (Причорноморський науково-дослідний інститут економіки та інновацій, 2021)
У статті розглянуто актуальні теоретичні питання про необхідність та важливість розроблення маркетингової стратегії промислового підприємства, проаналізовано наукові позиції вітчизняних та зарубіжних учених щодо сутності поняття «маркетингова стратегія». Обґрунтовано основні фактори, що впливають на маркетингову стратегію, котра забезпечує підвищення конкурентоспроможності промислового підприємства на ринку. Виділено основні методи формування маркетингової стратегії та чинники, які впливають на вибір тієї чи іншої стратегії. Визначено основні завдання, що підлягають вирішенню в процесі розроблення маркетингової стратегії промислового підприємства. Розглянуто методи якісного аналізу ринку, представлено інструменти визначення рівня конкуренції і виділення основних гравців ринку. Продемонстровано вплив конкуренції на маркетингову стратегію. Розглянуто теоретичні аспекти підвищення конкурентоспроможності підприємства в умовах ринку.

The article describes the urgent theoretical questions about the importance of developing a marketing strategy for industrial enterprises. The basic theoretical concepts and domestic and foreign scientists’ main positions about the nature of the term “marketing strategy” have been analyzed. Substantiates the most important factors influencing the marketing strategy, which ensures the competitiveness of enterprises on market. Highlights the main methods for developing a marketing strategy and the factors that influence the choice of a strategy have been pointed out. Defines the main objectives that have to be accomplished during the development of marketing strategy for industrial enterprises. Reviews the methods of market analysis, lists the instruments for defining market competition level and finding the major market players. Demonstrates the impact of competition on marketing strategy. Reviews the theoretical aspects of increasing the enterprise’ competitiveness on the market. In order to develop a marketing strategy for the enterprise, which matches the competitive conditions, market characteristics and targeted on increasing the competitiveness and effectiveness of industrial enterprise operation, it highlights the main method for marketing strategy development. Nowadays, the question of increasing of the enterprise’ competitiveness becomes more important and valuable, and also requires improvements and adaptation to market conditions, which change rapidly. The enterprise’ ompetitiveness analysis is obligatory for dominance on a market. Further research has to be focused on developing the methodical approach to creating the strategic profile of the industrial enterprise. Mainly the increase of product competitiveness is achieved competitiveness factors which include product quality, pricing, marketing strategy, market research, services. For developing a competitive business, it is important to not only upgrade the production and management, but also clear understanding of goals to be achieved. The most important should be the ability to define, rapidly and effectively use its advantages in market competition.
Developing a marketing strategy for industrial enterprises for ensures the competitiveness
Keywords: стратегія; ефективність; маркетинг; конкурентоспроможність; ринок; маркетингова стратегія; споживачі; аналіз; зовнішнє середовище; внутрішнє середовище; strategy; marketing; competitiveness; efficiency; market; marketing strategy; consumer; analysis; external environment; internal environment